Appraisals of insomnia identity in a clinical sample. (October 2021) - Emert, Sarah E.; Gunn, Heather E.; Molzof, Hylton E.; Dietch, Jessica R.; Lichstein, Kenneth L.
Abstract: Background: Insomnia identity, the conviction that one has insomnia, occurs independently of sleep quality or quantity, and is associated with numerous negative health outcomes. Little is known about factors influencing insomnia identity. This study planned to evaluate insomnia identity, perceived sleep experience, and sleep parameters. Method: Individuals seeking treatment for an insomnia complaint reported demographics, insomnia identity ratings, and daily sleep diaries. Insomnia complaint and insomnia identity were independently crossed with sleep diary data yielding: complaining good ( n = 10) and poor sleepers ( n = 51), and good ( n = 7) and poor sleepers ( n = 40) with insomnia identity. Participants were additionally classified as with ( n = 50) and without ( n = 14) insomnia identity. Group differences and predictors of insomnia identity were assessed. Results: Complaining poor sleepers and poor sleepers with insomnia identity reported significantly poorer sleep ratings compared to their counterparts. Insomnia identity severity was predicted by worse sleep quality comparisons and increased helplessness. Analyses revealed poorer sleep parameters among those with an insomnia identity versus without. Discussion: Group differences may reflect variation in perceived sleep assessment and insomnia identity rating. Results further indicated that not all who complain of insomnia (and seek treatment) endorse insomnia identity. Implications of results and future study directions on insomnia identity are discussed. Highlights: Not all who endorse insomnia complaints have an insomnia identity. People with insomnia identity reported worse insomnia-related symptoms. Good sleepers, with insomnia complaint or insomnia identity, report better sleep. Poor-quality sleep comparisons and helplessness predicted insomnia identity.